(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In today’s world when focus is on reducing self-weight of concrete, light weight concrete has come with the high number of applications to reduce self weight of concrete. In this study an attempt has been made to compare conventional concrete with the lightweight concrete which is made by partially replacing cement with fly ash and coarse aggregate with pumice stone and adding Thermocol beads using M25 grade of concrete. Lightweight concrete has been made by partial replacement of Coarse aggregate by pumice stone varying in the ratio of 10% 15% and 20% and Thermocol beads by 0.2%, 0.4% and 0.6%.Also cement is replaced by fly ash in the varying ratios of 20% 30% and 40% by weight of cement. In addition to that fine aggregate is replaced by Thermocol beads in the varying ratios of 0.2%, 0.4%and 0.6%.